"Beasts in Human Form": How Dangerous Speech Harms - Marques, Teresa (Araucaria, 2019)
Recent years have seen an upsurge of inflammatory speech around theworld. Understanding the mechanisms that correlate speech with violence isa necessary step to explore the most effective forms of counterspeech. Thispaper starts with a review of the features of dangerous speech and ideology, asformulated by Jonathan Maynard and Susan Benesch. It then offers a conceptualframework to analyze some of the underlying linguistic mechanisms at play:derogatory language, code words, figleaves, and meaning perversions. It givesa hypothesis for assessing the moral responsibility of interlocutors in dangerousspeech situations. The last section applies this framework to the case ofdemagogic discourse by Catalan nationalists. The framework offered explainshow public discourse in Catalonia has harmed social relations and institutions,and is an obstacle to rational resolutions to the political situation.